On Certain Applicable Aspects of Ideal Convergence - Adhikary, Nayan; Pal, Sudip Kumar (Sarajevo Journal of Mathematics, 2022)
In this article we present certain results involving existence of common fixed points, characterization of equicontinuous family and generalized integration, all using the notion of ideal convergence.